Native and decellularized porcine vena cava: Histological analysis and in vitro repopulation - Massaro, Maria Stefania; Pálek, Richard; Malečková, Anna; Grajciarová, Martina; Červenková, Lenka; Polák, Robert; Šarčević, Sima; Ševčík, Jan; Bolek, Lukáš; Tonar, Zbyněk; Liška, Václav; Moulisová, Vladimíra (Biomaterials advances, 2025)
Current standards in vascular reconstruction imply the use of autologous or synthetic material. Despite being standard, autologous grafts are limited by pathologies already affecting the patient and possible complications at the site of explantation, while synthetic grafts carry increased infection risks. Decellularized tissues have gained significant attention due to their potential for improving integration and functionality. The decellularization process removes cellular components while retaining the extracellular matrix, providing a scaffold that supports endothelial cell growth and minimizes immune rejection. Porcine decellularized vena cava is a promising candidate for vascular graft applications due to its structural similarity to human blood vessels and biocompatibility. In this study, we decellularized porcine vena cava with a combination of Triton X-100 and sodium dodecyl sulfate in four hours. We subsequently characterized the wall structure through histological stainings and proteomic analysis. Parameters such as wall thickness, intima-media layers thickness, collagen and elastin area fraction were quantified and compared. Moreover, decellularized veins were repopulated in vitro with human endothelial cells in static and dynamic conditions to verify the adhesion of human cells to the porcine scaffold and fully functionalize the lumen. An in-house-designed bioreactor was developed to seed endothelial cells on the lumen, mimicking the in vivo blood flow.
Keywords: prasata; Tissue Engineering; Swine; endoteliální buňky pupečníkové žíly (lidské); Venae Cavae; Endothelial Cells; endoteliální buňky; venae cavae; Bioreactors; decelularizovaná extracelulární matrix; Bioreactor repopulation; Human Umbilical Vein Endothelial Cells; extracelulární matrix; bioreaktory; tkáňové inženýrství; kultivované buňky; Animals; lidé; Humans; zvířata; Extracellular Matrix; Tissue Scaffolds; Porcine vena cava; Histological analysis; Cells, Cultured; Decellularization; tkáňové podpůrné struktury; Proteomics; Decellularized Extracellular Matrix